Hydroxyl-functionalized polyaniline nanospheres: tracing molecular interactions at the nanosurface via vitamin C sensing - Anilkumar, P.; Jayakannan, M. (Langmuir, 2008)
Here, we report a synthesis of novel polyaniline nanospheres bearing mono- and bishydroxyl functional groups were to trace the molecular interactions at the nanosurfaces through vitamin C sensing. Two new aniline monomers synthesized via a tailor-made approach and polymerized to produce soluble and uniform polyaniline nanospheres. The structures of the monomers and polymers were characterized by NMR, FT-IR, and MS techniques, and the morphology of the nanomaterials was analyzed by SEM and TEM. The mechanistic aspects of the nanomaterial formations were analyzed by FT-IR and dynamic light scattering techniques. These studies revealed that the hydroxyl-functionalized monomers have strong hydrogen bonding at the monomer level and form spherical aggregates in water, which are templates for the polyaniline nanospheres 600 +/- 100 nm in size. A controlled synthesis was also carried out using aniline hydrochloride as an unsubstituted counterpart, which yields polyaniline nanofibers. WXRD analysis confirmed the presence of a sharp peak at lower angle at 2 theta = 7.3 degrees (d-spacing of 13.4 angstrom) in hydroxyl-substituted nanospheres with respect to enhancement of solid-state ordered crystalline domains, whereas unsubstituted nanofibers were found to be highly amorphous. Vitamin C was employed as an analyte to trace the molecular interaction at the nanosphere surface and Study the influence of nanosurface functionalization on the sensing ability of biomolecules. The bishydroxyl-functionalized polyaniline nanospheres were found to show efficient molecular interactions toward vitamin C, whereas nanospheres with a monohydroxyl group or unsubstituted nanofibers failed as sensing materials. In a nut shell, in the present investigation, for the first time, we have proved the importance of surface functionalization of polyaniline nanomaterial, exclusively nanospheres, using hydroxyl groups for studying the molecular interactions at the nanosurfaces with biomolecules such as vitamin C.